Everyday politics in public administration - Miller, Hugh T. (1993)
The politics-administration dichotomy was long ago dismissed as either a descriptive or (except for a few notable holdouts) prescriptive account of what the role of public administration should be. Political involvement - coalition formation, symbol manipulation, constituency mobilization - by public administrators is an everyday occurrence. Political engagement remains problematic for public administrators, however. If political involvement is permitted, someone will have to rethink the meaning of Progressivism, neutral competence, professionalism, and an expert-based civil service. A healthy public discourse preserves and creates an authentic polis that is able to focus on community aims and purposes
Keywords: Civil service - United States; Bureaucracy - United States; Public administration - United States